Community awareness, perceptions, and behavior regarding antibiotic consumption in an urban area of Pondicherry - C. Niranjhanadevi; P. Stalin (Journal of Current Research in Scientific Medicine)
Background: Inappropriate use of antimicrobials is one of the important contributing factors for antimicrobial resistance (AMR). The role of the community in the development of AMR is very significant and needs to be understood. The study aimed to determine the level of awareness, perception, and behavior regarding antibiotic usage among the community members and to identify the association between sociodemographic factors and knowledge. Materials and Methods: A cross-sectional study was conducted among adults in an urban area of Pondicherry. Eligible study participants were selected by multistage random sampling and interviewed through a house-to-house survey using a structured questionnaire using Epicollect5 software. The study protocol was approved by the institutional ethics committee (RC/2022/07). Student’s t-test and ANOVA were used to calculate P values. Results: Among 440 study participants, 286 (65%) said that they had ever heard of a type of medicine called antibiotics. Among them, more than 70% of participants were aware that antibiotics are used for killing germs but almost all said that antibiotics are often needed for cold and flu illnesses. 83.2% opined that they should take antibiotics to prevent getting a serious illness. 42.3% of the study participants never completed a full course of antibiotic treatment after feeling better with a few doses. Participants with higher education and upper socioeconomic status had better knowledge than others. Conclusion: Overall knowledge of the study participants was found to be inadequate. Most of the study participants did not have a correct attitude toward the use of antibiotics. The majority of the study participants were not following appropriate practices toward the use of antibiotics.